Graphene-MnFe2O4-polypyrrole ternary hybrids with synergistic effect for supercapacitor electrode. (10th August 2019) - Thu, Tran Viet; Van Nguyen, To; Le, Xuan Duong; Le, The Son; Van Thuy, Vu; Huy, Tran Quang; Truong, Quang Duc
Abstract: Hybridization of dissimilar materials is a promising solution to improve desired properties in various applications. Herein, we chemically grew a conductive polymer (polypyrrole, PPy) on graphene-supported manganese ferrite microspheres (MG, ∼344 nm in size) to form PPy/MG hybrids at various PPy contents (20, 33.3, and 42.9 wt%). PPy, MG binary, and PPy/MG ternary hybrids were comprehensively characterized to correlate their structure, morphology, and properties. Electrochemical measurements revealed a significantly enhancement of capacitive performances of PPy/MG as comparison to those of each component. Consequently, the combination of PPy and MG resulted in maximum specific capacitance of 147.2 F/g at scan rate of 10 mV/s or 66.1 F/g at current density of 0.5 A/g. These synergistic and cooperative effects are attributed to reduced diffusion resistance in the PPy/MG hybrids. This work thus suggests an efficient strategy to develop high-performance material for supercapacitor electrode.